Studies in Germanic, Indo-European and Indo-Uralic - Kortlandt, Frederik (Leiden studies in Indo-European ;, 2010)
The red thread which runs through this book is a quest for relative chronology of linguistic developments. The probability of a reconstruction can be judged against the background of the transitions which it implies for the linguistic system as a whole. The reconstructions are always bottom-up, never top-down. It follows that the chapters on Germanic can be read without reference to the Indo-European background and that the Indo-Uralic part of the book can be left out of consideration if one does not want to look beyond Proto-Indo-European. The initial chapters of the book offer an introductio.